Personalistyczna koncepcja społeczeństwa u Jana Pawła II w kontekście wybranych obszarów relacji lekarz-pacjent - Burda-Świerz, Katarzyna; Kapias, Michał (Annales. Etyka w Życiu Gospodarczym, 2010)
Considering world’s social and ethical problems, it is unavoidable to omit the area of medical issues in which biological and therapeutic revolution took place. Pope John Paul II points out indirectly that doctor–patient relationship should be held with the respect for ethical and legal requirements because of human dignity, which is the principle, cause, goal and sense of all reality. In order to arrange the interrelation between the doctor and the patient in an appropriate way, it is necessary to build bonds between them. Those bonds create patient’s and doctor’s participation in the process of medical treatment. The aim of this article is to present some aspects of Personalism by John Paul II (social doctrine of the Church) in patient–doctor relationship. The main reference point for considering aspects of patient–doctor relationship is the communitarian dimension of human being as a person in Karol Wojtyła’s philosophy.